Performance of a PCR Assay for Detection of Pneumocystis carinii from Respiratory Specimens - Caliendo, Angela M. (American Society for Microbiology, 1998)
This study evaluates the performance of a PCR assay for the detection of Pneumocystis carinii from respiratory specimens that has been designed for use in the clinical microbiology laboratory. The test includes a simple method for nucleic acid extraction and amplification, a colorimetric probe hybridization technique for detection of amplicons, and an internal control to evaluate for the presence of inhibitors of amplification. Two hundred thirty-two clinical specimens (120 induced-sputum [IS] and 112 bronchoalveolar lavage [BAL] specimens) from 168 patients were tested by both immunofluorescent (direct fluorescent-antibody [DFA]) staining and PCR. Of the 112 BAL specimens, 17 were positive for P. carinii by DFA staining and PCR. An additional two specimens were DFA negative and PCR positive. For BAL specimens, the sensitivity and specificity of PCR compared to DFA were 100 and 98%, respectively. Eighteen IS specimens were positive for P. carinii by DFA, and 27 were positive by PCR. One of the 18 DFA-positive IS specimens was negative by PCR; this patient had just completed therapy for P. carinii pneumonia. Of the 10 specimens that were PCR positive and DFA negative, 4 were from patients who had a subsequent BAL specimen that was positive by DFA and PCR. For IS specimens, the sensitivity of DFA and PCR was 82 and 95%, respectively. The specificity of PCR for IS specimens was 94%. Due to the high sensitivity of PCR for the detection of P. carinii from IS specimens, a PCR-based diagnostic test may be a useful screening test and may alleviate the need for bronchoscopy in some patients.